Development of Customer Development Stages in Tourism Directory Application Services Using Design Thinking - Made Agung Dharma Sentosa; Firman Hawari (Publikasi Indonesia, 2024)
The Development of Customer Development Stages in the Tourism Directory Application Service using Design Thinking is a development process based on the stages of a survey of user needs in defining problems and formulating solutions to these problems. This research aims to gain knowledge and insight related to user needs for a tourist directory application service, identify service features that are by the needs of tourist directory application service users, and obtain a Minimum Viable Product (MVP) on the tourist directory application service owned by the current author (https://gatewee.com). The research conducted is in the form of surveys and interviews with users through the stages of Customer Development and uses a user-based problem-solving approach through Design Thinking. Methods This research is qualitative and quantitative research that describes the user-based development strategy of the Tourism Directory Application Service. The results of the research are User Persona, identification of features, focus on feature development, prototypes, Usability Test results, MVP, targeting strategies & business models and business development plans.